CLINICAL AND GENETIC CHARACTERISTICS OF MUCOLIPIDOSIS II AND IIIA TYPES IN CHILDREN - A. N. Semyachkina (Rossijskij Vestnik Perinatologii i Pediatrii, 2017)
The article is devoted to a rare pathology from a group of accumulation diseases with an autosomal recessive type of inheritance – mucolipidosis II and IIIA types. The disease is characterized by a greater phenotypic similarity to mucopolysaccharidosis.Objective: analysis of genophenotypic parameters in Russian patients with mucolipidosis II and IIIA types. The activity of lysosomal enzymes in plasma (β-glucuronidase, total hexosaminidase and N-acetyl-α-D-glucosaminidase) was measured using a standard technique using chromogenic and fluorogenic substrates. Genomic DNA of peripheral blood leukocytes was isolated using a set of reagents Preb 100 (DIAtomTM). Amplification of all exons of the GNPTAB gene was carried out by polymerase chain reaction (PCR) followed by direct non-radioactive sequencing by Sanger.50 patients aged from 1.5 to 10 years were examined. The clinical symptoms of the disease included: a Hurler-like phenotype, growth retardation, skeletal, cardiac and vascular damage, and CNS. Mucolipidosis type II (I-cell disease) was characterized by a more severe course. The clinical diagnosis was confirmed by the results of laboratory methods of investigation: normal parameters of renal excretion of glycosiminoglycans (GAG), high (5-15 times higher than normal) activity of lysosomal hydrolases in blood plasma and detection of mutations in the GNPTAB gene.35 probands are completely genotyped. In 8 patients only 8 mutant alleles were detected; 7 mutations were not detected. Six new mutations in exons 1 (p.I31N; p.Q36P), 10 (p.L398P), 11 (p.W446X) and 13 (p.S738X; c.2250delT) were found, including a frequent mutation for Russian patients P.S738X (21% alleles). The most common (31.4% alleles) in the Russian cohort of patients was a known small deletion c. 3503_3504delTC, leading to a reading frameshift.A clinical observation of a child with type 2 mucolipidosis (I-cell disease) with typical symptomatology of the disease caused by two nonsense mutations of the GNPTAB gene is presented: p.S738X / p.R375X.In conclusion, it is emphasized that the identification of mutations of the GNPTAB gene provides prediction of the severity of the disease course, an understanding of the mechanisms of its development that will contribute to the development of pathogenetic treatment methods, improving the quality of life of patients and effective medical and genetic counseling.